The dependence of arctic mixed phase stratus ice cloud microphysics on aerosol concentration using observations acquired during ISDAC and M-PACE - Jackson, Robert (2011)
Data acquired by the National Research Council of Canada (NRC) Convair-580, equipped with cloud and aerosol probes during 5 sorties through single-layer arctic stratocumulus on 8 April, 18 April, and 26 April 2008 during the Indirect and Semi Direct Aerosol Campaign (ISDAC) and by the University of North Dakota Citation on 4 sorties on 9, 10 and 12 October 2004 during the Mixed Phase Arctic Cloud Experiment (M-PACE) were used to test three aerosol indirect effects hypothesized to act in mixed phase clouds: the riming indirect effect, the glaciation indirect effect, and the cold second indirect effect. By comparing liquid and ice particle size distributions (SDs) measured by different probes and by conducting mass closure tests where masses derived from size and shape distributions are compared against mass contents measured by bulk probes, a best estimate of the number concentration of water (Nl) and ice particles (Ni), liquid (Nl(D)) and ice crystal (Ni(D)) SDs, liquid effective radius rel, and liquid (LWC) and ice water content (IWC). For the ISDAC cases, the cloud properties were then examined as a function of ambient accumulation mode aerosol concentrations Na above and below the cloud measured by a Passive Cavity Aerosol Spectrometer Probe (PCASP), cloud condensation nuclei (CCN) concentrations from a CCN counter, and ice nuclei (IN) concentrations from a Continuous Flow Diffusion Chamber (CFDC). The data showed a positive correlation of 0.77 between Nl inside cloud and Na below cloud. This, combined with an increase of LWC with height above cloud base and the nearly constant profile of Nl, showed that liquid drops were likely nucleated from aerosol at cloud base. No strong correlation between in cloud IWC and Na above or below cloud was seen, indicating no evidence of a riming indirect effect for the ISDAC single-layer stratus. A strong correlation of 0.69 between Ni and aerosol concentration above cloud was noted. Provided that IN increases with NPCASP above cloud, this combined with the subadiabatic ...